Poly(N, N-dimethylacrylamide-octadecyl acrylate)-clay hydrogels with high mechanical properties and shape memory ability. Issue 30 (8th May 2018) - Wang, Feng; Yong, Xueyong; Deng, Jianping; Wu, Youping
Abstract : As a type of important intelligent materials, shape memory hydrogels (SMHs) have gathered a lot of interest due to their promising applications. Abstract : As a type of important intelligent materials, shape memory hydrogels (SMHs) have gathered a lot of interest due to their promising applications. However, preparing SMHs with excellent mechanical properties still remains a big challenge. In this study, a new type of SMHs with excellent mechanical strength is created. The SMHs were prepared by free radical micellar polymerization of hydrophobic monomer (octadecyl acrylate) with gelatin as emulsifier in a aqueous system containing hydrophilic monomer ( N, N -dimethylacrylamide, DMA) and clay as reinforcing filler. The polymerization provided physically cross-linked network structures constructed by two non-covalent interactions, i.e. hydrophobic association formed by monomer units and multiple H-bonds among inorganic clay, gelatin and DMA. A judicious combination of the two physically cross-linked networks significantly improved the mechanical strength of hydrogels. More interestingly, the hydrogels demonstrated shape memory behavior due to the hydrophobic poly(octadecyl acrylate) domains. The novel SMHs are expected to find practical applications as biomaterials.